Pengaruh Artifical Intelligience terhadap Efisiensi Audit Keuangan Syariah - Bagus Septiawan, Ardian; Nurul Majid, Muhammad; Abiel Adib Muhammad, Daulat; Arwani, Agus (Risalah Iqtishadiyah, 2025)
This study aims to explore how the application of Artificial Intelligence (AI) affects the level of efficiency in the audit process in the Islamic-based financial system. Amid the rapid development of digital technology, the use of AI in accounting and auditing practices is becoming increasingly common, including in the Islamic financial sector. This research uses a qualitative approach with a literature study method, namely by reviewing various relevant literature sources, scientific articles, and previous research results. The results of the analysis show that the utilization of AI can speed up the audit process, improve the accuracy of results, and assist in the identification of risks earlier. However, its application still requires control from human auditors to remain in line with sharia principles. This research is expected to be a reference for auditors and Islamic financial institutions in integrating technology wisely while maintaining sharia values.